Interrelations of calcium-regulating hormones during normal pregnancy. Issue 6283 (4th July 1981) - Whitehead, M; Lane, G; Young, O; Campbell, S; Abeyasekera, G; Hillyard, C J; MacIntyre, I; Phang, K G; Stevenson, J C
Abstract : Profound changes in calcium metabolism occur during pregnancy. The mother has to make available extra calcium for fetal requirements while ensuring that her plasma and bone calcium concentrations are satisfactorily maintained. In a cross-sectional study plasma concentrations of the major calcium-regulating hormones--namely, calcitonin, parathyroid hormone, 25-hydroxyvitamin D (25-OHD), and 1, 25-dihydroxyvitamin D (1, 25-(OH)2D)--were measured to establish their interrelations during normal pregnancy. The major changes observed were increases in the circulating concentrations of 1, 25-(OH)2D and calcitonin. Concentrations of parathyroid hormone and 25-OHD remained within the normal range. The increased concentrations of 1, 25-(OH)2D enable the increased physiological need for calcium to be met by enhancing intestinal absorption of this element. The simultaneous rise in calcitonin opposes the bone-resorbing activities of 1, 25-(OH)2D, thereby protecting the integrity of the maternal skeleton. Maternal calcium homeostasis is thus maintained yet the requirements of the fetus are fulfilled.